Multi-Dimensional Approach To Hyperacidity & Indigestion Conquer With Homoeopathy (Homoeopathy for All, 2025)
Hyperacidity is also called Acid  Dyspepsia, which is one of the most  common problem. Hyperacidity  is a medical condition in which  the stomach secretes a lot of acids.  Homoeopathy is a remarkable  resource for those dealing with  digestive disorders. Homoeopathy  can be of assistance in retrieving  normal motility and treating any  psychological issues related to  gastric disorders.
Keywords: Dyspepsia; Gallstones; Peptic ulcers; Antiinflammatory medicines